Cardiac Rehabilitation in Frail Older Adults With Cardiovascular Disease: A NEW DIAGNOSTIC AND TREATMENT PARADIGM. Issue 2 (March 2020) - Flint, Kelsey M.; Stevens-Lapsley, Jennifer; Forman, Daniel E.
Abstract : Older adults with cardiovascular disease (CVD) pose challenges to cardiac rehabilitation (CR) clinicians because their disease is often coupled to physical frailty. Older patients with CVD and frailty may be less likely to tolerate conventional CR exercise training due to multidimensional (ie, strength, mobility, and balance) physical impairments. Furthermore, conventional CR typically emphasizes endurance training without addressing the intrinsic skeletal muscle impairments of frail patients that often manifest as deficits in strength, mobility, and balance, undercutting feasibility and any likely benefits. However, if appropriately modified to meet the needs of frail older adults, CR may be a powerful tool for this challenging population. To best serve frail, older adults with CVD, CR programs can incorporate well-validated strategies to assess frailty and physical function that also fit within the workflows and patient populations of individual programs. Such frailty assessments provide opportunities to identify specific targets (eg, weakness) that need to be addressed before a subsequent aerobic training program can be successfully implemented and sustained. The current review focuses on the use of physical frailty measures in older adults with CVD, with practical considerations for their clinical use in contemporary CR, as well as directions for future research. Abstract : Older adults with cardiovascular disease are also often frail, with multidimensional physical deficits that may preclude meaningful participation in standard cardiac rehabilitation (CR). This review focuses on enhanced physical function assessments in older CR patients to better recognize frailty as a clinical target that can potentially be addressed more effectively with novel CR approaches.